Solasonine Suppresses the Proliferation of Acute Monocytic Leukemia Through the Activation of the AMPK/FOXO3A Axis - Zhang, Hong; Tian, Fang; Jiang, Pengjun; Qian, Shushu; Dai, Xingbin; Ma, Bangyun; Wang, Mengya; Dai, Huibo; Sha, Xiaocao; Yang, Zhongfa; Zhu, Xuejun; Sun, Xuemei (Frontiers in Oncology, 2021)
Solasonine, the main active ingredient of Solanum nigrum L, has been reported to exert extensive antitumor activity. However, the antitumor effects in acute monocytic leukemia and the exact mechanisms involved are unknown. In this study, we investigated the role of solasonine on inhibiting the progression of acute monocytic leukemia. Our findings showed that solasonine inhibited the proliferation of acute monocytic leukemic cell lines (THP-1 and MV4-11) in vitro. Solasonine promoted apoptosis and induced cell cycle arrest in the G2/M phase. Analysis of RNA-seq data suggested that solasonine correlated with increased expression of genes in the AMPK/FOXO3A pathway. Inhibition of AMPK with compound C followed by treatment with solasonine showed that solasonine reduced apoptosis, caused less cell cycle arrest, and inactivated the AMPK/FOXO3A axis in THP-1 and MV4-11cells. Solasonine also inhibited tumor growth by the activation of the AMPK/FOXO3A axis. In conclusion, solasonine inhibited the progress of acute monocytic leukemia in vitro and in vivo and triggered the apoptosis and cell cycle arrest in the G2/M phase by upregulating the AMPK/FOXO3A pathway.